RECENT ADVANCES IN PIN FIN APPLICATIONS FOR HEAT TRANSFER ENHANCEMENT - Obayopo, S. O.; Akintunde, S.; Adewoyin, A.; Onojowho, E. E.; Julius, M. (Proceedings of the OAU Faculty of Technology Conference 2017, 2017)
Heat transfer enhancement has played a critical role in many industrial application to improve system performance and heat recovery processes. The quest for improved heat recovery in the industry and alternative energy systems has necessitated the need to explore more sophisticated heat transfer enhancement approaches towards optimal system. This review article presents a broad assessment and critical review of past researches on pin fin enhancement basically to provide a comprehensive understanding of pin fin as an important application tool in various areas in the thermal science field and industry including power generation, high power electronics cooling, refrigeration and air-conditioning, nuclear reactors, etc. Several heat transfer enhancement techniques have been reported in the literature in recent times with practical application challenges such as machinability, pressure drop concerns and identification of industrial cost towards implementation. The important achievements, inconsistences and contradictions from the literature in these heat transfer area are identified and discussed. These provide basis for immediate research needs and identified area of future researches in pin fin application for enhanced heat transfer.
A REVIEW OF RECENT PROGRESS
Keywords: Heat transfer; Enhancement; Pin fins; System performance; Heat recovery; Industrial applications